The Yangtze River Delta market integration and farmers ’ income increase - Yao, Xumin (International Journal of Global Economics and Management, 2024)
Market integration is of great significance to increase farmers’ income. Taking 27 core cities in the Yangtze River Delta from 2011 to 2021 as an example, an evaluation index system of market integration including 8 indicators is constructed from three perspectives: regional connection, scientific and technological innovation and environmental regulation, and the entropy method is used to comprehensively evaluate the level of market integration. The measurement results show that the level of market integration in the Yangtze River Delta is still severe, and the internal differences are large. Using two-way fixed effects, it is found that the level of market integration can significantly and positively affect the per capita disposable income of rural residents, and pass the robustness test; heterogeneity analysis found that the level of market integration can significantly positively affect high-level income rural residents, but not significantly affect low-and middle-income rural residents. Suggestions are put forward from the perspectives of optimizing market integration policy, paying attention to middle and low income farmers, and coordinating regional development, so as to provide reference for policy implementation path.